The ABCD of Obesity: An EASO Position Statement on a Diagnostic Term with Clinical and Scientific Implications - Frühbeck, Gema (Obes Facts, 2019)
Obesity is a frequent, serious, complex, relapsing, and chronic disease process that represents a major public health problem. The coining of obesity as an adiposity-based chronic disease (ABCD) is of particular relevance being in line with EASO's proposal to improve the International Classification of Diseases ICD-11 diagnostic criteria for obesity based on three dimensions, namely etiology, degree of adiposity, and health risks. The body mass index as a unique measurement of obesity does not reflect the whole complexity of the disease. Obesity complications are mainly determined by 2 pathological processes, i.e., physical forces (fat mass disease) as well as endocrine and immune responses (sick fat disease), which are embedded in a cultural and physical context leading to a specific ABCD stage.